Efficient perovskite solar cell and printing preparation method thereof

By introducing DMAPbI3 intermediates in the printing and preparation of perovskite solar cells, the growth of perovskite crystals is regulated, and the problem of improvement of perovskite solar cells is solved, and the significant improvement of FF and PCE has been achieved.

CN119403412AActive Publication Date: 2025-02-07SHAANXI NORMAL UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411478236.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-07
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The performance of perovskite solar cells in the prior art has not yet reached the theoretical limit, especially the filling factor (FF) has a large room for improvement.

Method used

During the printing and preparation of perovskite solar cells, DMAPbI3 intermediate is introduced to increase grain size and reduce defects by regulating perovskite crystal growth, thereby improving the FF and photoelectric conversion efficiency (PCE) of solar cells.

Benefits of technology

By introducing the DMAPbI3 intermediate, the FF of FA1-x-yCSxMAyPbI3-xBrx perovskite solar cells was significantly improved from 73.88% to 81.42%, and the series resistance of the device was reduced, improving carrier transport capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119403412A_ABST
    Figure CN119403412A_ABST
Patent Text Reader

Abstract

The invention discloses an efficient perovskite solar cell and a printing preparation method thereof, and belongs to the technical field of perovskite solar cells. According to the method, a part of DMAPbI3 intermediate is introduced in the preparation process of the FA1-x-yCSxMAyPbI3-xBrx (x is 0.05, and y is 0.02-0.06) perovskite absorption layer, so that the growth process of perovskite crystals is effectively regulated and controlled, the grain size of the perovskite thin film is remarkably increased, and in-situ passivation of thin film defects is realized. Through a series of optimization measures, the filling factor and the photoelectric conversion efficiency of the FA < 1-x-y > CS < x > MAy PbI < 3-x > Br < x > perovskite solar cell prepared by blade coating in the atmospheric environment are finally improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy materials, and specifically relates to a high-efficiency perovskite solar cell and a printing preparation method thereof. Background Art

[0002] Perovskite solar cells (PSCs) have attracted extensive attention in the field of new energy due to their high photoelectric conversion efficiency (PCE) and low-cost manufacturing potential. However, the current FA prepared by blade coating 1-x-y C Sx MA y PbI 3-x Br x The photoelectric conversion efficiency of perovskite solar cells is still insufficient compared to traditional spin coating methods. In roll-to-roll production, the PCE of the cell becomes a key factor in determining the cost of power generation, among which the improvement of the fill factor (FF) is particularly important.

[0003] According to the Shockley-Queisser (SQ) limit theory, there is a theoretical upper limit on the performance parameters of PSCs with a specific band gap. 1-x-y C Sx MA y PbI 3-x Br x After the formation of perovskite solar cells, the performance parameters of perovskite solar cells have not yet reached the SQ limit, especially FF, which has a large room for improvement, but there is little research on the related issues. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a high-efficiency perovskite solar cell and a printing preparation method thereof, so as to solve the problem that the performance of perovskite solar cells in the prior art still has a large room for improvement. The method introduces DMAPbI3 intermediates during the perovskite crystallization process to regulate the growth of perovskite crystals, effectively increases the grain size of the perovskite film, reduces defects, and thus improves the efficiency of preparing FA by scraping under atmospheric conditions. 1-x-y C Sx MA y PbI 3-x Br x FF and PCE of PSCs.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A printing preparation method for a high-efficiency perovskite solar cell comprises the following steps:

[0007] Step 1, pre-treating the FTO glass substrate;

[0008] Step 2, immersing the FTO glass substrate in a TiCl4 aqueous solution to grow TiO2, and preparing a TiO2 electron transport layer after annealing;

[0009] Step 3, dissolving FAI, CsBr, PbI2 and MACl in a solvent according to a set molar ratio, wherein the solvent is a mixed solution of N,N-dimethylformamide, dimethyl sulfoxide and 2-methyltetrahydrofuran, and then adding (3,5-difluorophenyl) potassium trifluoroborate to obtain an intermediate engineering perovskite solution, adding DMAPbI3 to the intermediate engineering perovskite solution, and stirring to obtain FAI added with DMAPbI3 1-x-y C Sx MA y PbI 3-x Br x Perovskite precursor solution, FA 1-x-y C Sx MA y PbI 3-x Br x In the example, x is 0.05 and y ranges from 0.02 to 0.06;

[0010] Step 4, adding a perovskite precursor solution dropwise onto the TiO2 electron transport layer, applying the perovskite precursor solution by scraping with a scraper, blowing the solution after scraping, and annealing the solution after blowing to obtain a perovskite absorption layer;

[0011] Step 5, preparing a Spiro-OMeTAD hole transport layer on the perovskite absorption layer;

[0012] Step 6: Prepare a metal electrode on the hole transport layer.

[0013] A further improvement of the present invention is:

[0014] Preferably, in step 3, the added molar amount of DMAPbI3 is 1-30% of the molar amount of PbI2.

[0015] Preferably, in step 3, the volume ratio of N,N-dimethylformamide, dimethyl sulfoxide and 2-methyltetrahydrofuran is (5-8):1:(1-4).

[0016] Preferably, in step 3, the molar fraction of potassium (3,5-difluorophenyl) trifluoroborate in the perovskite precursor solution is 0.15-3%.

[0017] Preferably, in step 4, before scraping, the FTO glass substrate and the TiO2 electron transport layer are preheated on a hot plate at 40-120°C.

[0018] Preferably, in step 4, during the coating process, the distance between the scraper and the surface of the TiO2 electron transport layer is 10-500 μm.

[0019] Preferably, in step 4, during the blowing process, the air flow temperature is 20-40°C, the flow rate is 10-100m / s, and the duration is 3-30s.

[0020] Preferably, in step 4, the annealing temperature is 150° C. and the annealing time is 15 min.

[0021] Preferably, in step 5, a PEAI passivation layer is prepared before preparing the Spiro-OMeTAD hole transport layer.

[0022] A high-efficiency perovskite solar cell prepared by any of the above preparation methods, comprising an FTO glass substrate, a TiO2 electron transport layer, a FA 1-x-y C Sx MA y PbI 3-x Br x Perovskite absorber layer, Spiro-OMeTAD hole transport layer and metal electrode.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The invention discloses a printing preparation method for a high-efficiency perovskite solar cell. The method comprises the following steps: 1-x-y C Sx MA y PbI 3-x Br x DMAPbI3 (DMA + The structural formula is: (CH3)2NH2 + ) intermediate phase, which partially replaces PbI2 in the raw material, thereby introducing the DMAPbI3 intermediate phase during the perovskite crystallization process. Since the decomposition of the DMAPbI3 intermediate phase requires additional energy, the energy barrier for perovskite nucleation increases, thereby extending the perovskite crystal nucleation window. From the perspective of material growth dynamics, the extension of the nucleation process is beneficial to the transfer and diffusion of perovskite monomers, thereby promoting the increase of grain size. At the same time, the DMAPbI3 intermediate phase can also repair defects in situ, realizing the in-situ passivation of film defects. + and I -The effective filling of vacancies by ions during the crystallization process reduces non-radiative recombination losses and lowers the series resistance of the device. DMA can also enter the perovskite lattice by occupying the position of the A-site ions of the perovskite, thereby reducing the defect state density of the perovskite and improving the structural stability. Through the method of the present invention, the series resistance of the device was successfully reduced by 30%, significantly improving the carrier transport, and the printed FA in the atmospheric environment was 1-x-y C Sx MA y PbI 3-x Br x The FF of PSC was increased from 73.88% to 81.42%, and the PCE was also improved accordingly. This method has important scientific guidance significance and potential application value for the large-scale commercial production of perovskite in the future by regulating the crystallization of perovskite and passivating defects.

[0025] Furthermore, the perovskite absorption layer, passivation layer (PEAI) and hole transport layer are all prepared by the scraping method. Thanks to the regulation of crystallization dynamics and the synergistic effect of defect passivation, the scraping steps of the perovskite absorption layer and other layers can be carried out in an air environment at room temperature without the need for an additional inert atmosphere. This invention provides important guidance and promotion for the future commercial development of perovskite photovoltaic technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of the crystallization of the perovskite film prepared by the method described in Example 1 of the present invention and Comparative Example 1 before and after annealing.

[0027] Figure 2 The scanning electron microscope images of the perovskite film prepared by the method described in Example 1 of the present invention and Comparative Example 1 before and after annealing;

[0028] Among them, (a) is the comparative example 1 before annealing; (b) is the example 1 before annealing; (c) is the comparative example 1 after annealing; (d) is the example 1 after annealing.

[0029] Figure 3 The NMR images of the perovskite films prepared by the methods described in Example 1 and Comparative Example 1 before and after annealing are shown in FIG. 1 H spectrum.

[0030] Among them, (a) is the comparative example 1 before annealing; (b) is the comparative example 1 after annealing; (c) is the example 1 before annealing; (d) is the example 1 after annealing.

[0031] Figure 4 The in-situ ultraviolet-visible (UV-vis) absorption spectra of the perovskite films prepared by the methods described in Example 1 and Comparative Example 1 of the present invention during the scraping process.

[0032] Among them, Figure (a) is Comparative Example 1; Figure (b) is Example 1.

[0033] Figure 5 In-situ photoluminescence (PL) spectra of the perovskite films prepared by the methods described in Example 1 and Comparative Example 1 of the present invention during annealing.

[0034] Among them, Figure (a) is Comparative Example 1; Figure (b) is Example 1.

[0035] Figure 6 PL lifetime mapping results of the perovskite films prepared by the methods described in Example 1 and Comparative Example 1 of the present invention.

[0036] Among them, Figure (a) is Comparative Example 1; Figure (b) is Example 1.

[0037] Figure 7 The performance curve of the perovskite solar cell prepared by the method described in Example 1 of the present invention and Comparative Example 1 is shown.

[0038] Among them, (a) is the current density-voltage (JV) curve; (b) is the statistical distribution of photovoltaic device performance parameters of photoelectric conversion efficiency (PCE); (c) is the statistical distribution of photovoltaic device performance parameters of fill factor (FF); (d) is the statistical distribution of series resistance (R S )Statistical distribution of photovoltaic device performance parameters. DETAILED DESCRIPTION

[0039] The present invention is further described in detail below in conjunction with the accompanying drawings:

[0040] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0041] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0042] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0043] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0044] As the problem raised in the background technology, scraping FA 1-x-y C Sx MA y PbI 3-x Br x After forming the perovskite solar cell, for FA 1-x-y C Sx MA y PbI 3-x Br x The research on improving FF and PCE performance of perovskite solar cells is called. The improvement of FF is mainly affected by the charge extraction ability of PSC, the overall series resistance (R S ) and the impact of non-radiative recombination losses in devices, among which the grain size and defect state of perovskite films have a significant impact on FF and PCE.

[0045] In order to solve the above problems, the first aspect of the present invention discloses a printing preparation method for high-efficiency perovskite solar cells, which specifically comprises the following steps:

[0046] Step 1, cleaning and drying a fluorine-doped tin oxide (FTO) glass substrate as a conductive substrate;

[0047] Step 2, immerse the FTO / glass substrate in a TiCl aqueous solution at 50-80°C for 50-80 minutes. Then rinse the grown TiO2 with deionized water to prevent the TiO2 on its surface from continuing to grow. An overly thick electron transport layer will hinder charge transfer. The thickness of the electron transport layer is 10-50nm. Blow dry the rinsed TiO2 substrate with an air gun, and then place it on a hot plate at 150-300°C for annealing for 0.2-3h to remove moisture from the TiO2 surface and obtain a dense TiO2 electron transport layer.

[0048] Step 3, the preparation of the perovskite precursor solution is as follows: the perovskite compounds FAI, CsBr, PbI2 and MACl are mixed according to the FA 1-x-y C Sx MA y PbI 3-x Br xThe molar ratio of PbI2 is dissolved in 1 mL of a mixed solvent, the concentration of the solute is 0.7-1.2 M, wherein the solvent composition is N,N-dimethylformamide: dimethyl sulfoxide: 2-methyltetrahydrofuran = (5-8): 1: (1-4), and 0.15%-3% molar fraction of (3,5-difluorophenyl) potassium trifluoroborate is added to the perovskite solution to obtain an intermediate engineering perovskite solution, the intermediate engineering perovskite solution, DMAPbI3 is added to the intermediate engineering perovskite solution, the molar amount of DMAPbI3 added is 1-30% of the molar amount of PbI2, and after stirring, FA added with DMAPbI3 is obtained. 1-x-y C Sx MA y PbI 3-x Br x Perovskite precursor solution (Cl element is basically completely evaporated); in this process, DMAPbI3 is used to replace PbI2 to regulate the perovskite crystal growth process.

[0049] In the above process, the addition of 2-methyltetrahydrofuran and (3,5-difluorophenyl) potassium trifluoroborate can reduce the interaction between the perovskite solute and the solvent, so that in the subsequent annealing heat treatment process, the solvent can be fully volatilized, reducing the influence of the solvent on the crystallization of the perovskite absorption layer. However, because the solvent evaporates too quickly, it will accelerate the crystallization process of the perovskite, causing the crystallization of the perovskite to be too fast, and the crystallized perovskite particles to be too small, reducing the crystallization quality of the perovskite. By adding a small amount of DMAPbI3 to the perovskite, it is possible to delay the crystallization of the perovskite while ensuring that the solvent is fully removed, thereby forming a high-quality perovskite absorption layer.

[0050] Step 4, place the FTO / TiO2 substrate on a 40-120℃ hot stage for preheating for 3 minutes. The preheated substrate can promote the nucleation and crystallization of perovskite; then drop 6-20μL of perovskite precursor solution on the TiO2 / FTO substrate, and scrape it forward at a speed of 0.2-50m / min under the action of a scraper, and the distance between the scraper and the substrate is 10-500μm. The distance between the scraper and the substrate will affect the thickness of the scraped perovskite, and ultimately affect the crystallization quality of the perovskite film. Generally speaking, the thicker the scraped perovskite, the slower its crystallization speed. The scraped perovskite film is immediately treated with air blowing to accelerate the evaporation of the solvent, thereby reducing water erosion and promoting perovskite crystallization. The blowing process uses normal temperature airflow, the airflow temperature is 20-30℃, the flow rate is 10-100m / s, and the duration is 3-30s. After the coating, the perovskite film was immediately transferred to a hot plate at 150°C and heated for 10-25 minutes to promote the subsequent growth of perovskite.

[0051] Step 5, prepare a passivating agent solution of perovskite: dissolve 0.0005-0.0200 mg of phenylethylammonium iodide (PEAI) in 1 mL of isopropanol, shake for 12 hours in an atmospheric environment at 25° C., and set aside.

[0052] Step 6: Preheat the prepared perovskite on a 30-100°C hot plate for 3 minutes. At room temperature, drop 3.0-100 μL of PEAI solution on the perovskite film and scrape it forward at a speed of 1.5 m / min with a scraper. The distance between the scraper and the substrate is 10-500 μm.

[0053] Step 7, preparation of hole transport layer solution: add 90 mg Spiro-OMeTAD, 22 μL Li-TFSI solution (520 mg dissolved in 1 ml acetonitrile), 20 μL Co-TFSI solution (375 mg Co-TFSI dissolved in 1 ml acetonitrile) and 30 μL 4-tert-butylpyridine to 1 mL chlorobenzene and shake in air at 25 °C for 12 h.

[0054] Step 8, preheat the prepared perovskite on a 30-100°C hot plate for 3 minutes, drop 3.0-100 μL of Spiro-OMeTAD solution on the perovskite film, and scrape it forward at a speed of 1.5 m / min with a scraper, with the distance between the scraper and the substrate being 10-500 μm.

[0055] Step 9: Deposit a gold top electrode with a thickness of about 70 nm on the hole transport layer by thermal evaporation, with a vacuum degree of 9×10 –4 Pa, the evaporation rate is about 0.05nm / s. After the evaporation is completed, the battery is cooled in the vacuum chamber for 30 minutes and then taken out. The effective area of ​​each individual battery is 0.09cm 2 .

[0056] It includes a substrate, an electron transport layer, a perovskite light absorption layer, a perovskite passivation layer, a hole transport layer and a metal electrode stacked in sequence from bottom to top.

[0057] The following is further described in conjunction with specific embodiments.

[0058] Comparative Example 1

[0059] Step 1, cleaning and drying a fluorine-doped tin oxide (FTO) glass substrate for use as a conductive substrate;

[0060] Step 2, immerse the FTO / glass substrate in a TiCl aqueous solution at 70°C for 1 hour. Then rinse the grown TiO2 with deionized water to prevent the TiO2 on its surface from continuing to grow. An overly thick electron transport layer will hinder charge transfer. The thickness of the electron transport layer is 20nm. Blow dry the rinsed TiO2 substrate with an air gun, and then place it on a hot plate at 200°C for annealing for 0.5h to remove moisture from the TiO2 surface and obtain a dense TiO2 electron transport layer.

[0061] Step 3, the preparation of the perovskite precursor solution is as follows: 0.7M perovskite compounds FAI, CsBr, PbI2 and MACl are dissolved in 1mL of a mixed solvent at a molar ratio of 0.95:0.05:1:0.3, wherein the solvent composition is N,N-dimethylformamide: dimethyl sulfoxide: 2-methyltetrahydrofuran = 8:1:1, and 0.15% molar ratio of (3,5-difluorophenyl) potassium trifluoroborate is added to the perovskite solution.

[0062] Step 4, place the FTO / TiO2 substrate on a 60°C hot stage for preheating for 3 minutes, then drop 8.5μL of FAPbI3 precursor solution on the TiO2 / FTO substrate, and scrape it forward at a speed of 1.5m / min under the action of a scraper, and the distance between the scraper and the substrate is 80μm. The perovskite film after scraping is immediately treated with air blowing to accelerate the evaporation of the solvent, thereby reducing water erosion and promoting perovskite crystallization. The air flow temperature during the blowing process is 30°C, the flow rate is 20m / s, and the duration is 8s. The perovskite film after scraping is immediately transferred to a 150°C hot stage for heating for 15 minutes to promote the subsequent growth of perovskite.

[0063] Step 5, prepare a passivating agent solution of perovskite: dissolve 0.0030 mg of phenylethylammonium iodide (PEAI) in 1 mL of isopropanol, shake for 12 h in an atmospheric environment at 25° C., and set aside.

[0064] Step 6: Preheat the prepared perovskite on a hot plate at 40°C for 3 minutes. At room temperature, drop 6.0 μL of PEAI solution on the perovskite film and scrape it forward at a speed of 1.5 m / min with a scraper. The distance between the scraper and the substrate is 60 μm.

[0065] Step 7, preparation of hole transport layer solution: add 90 mg Spiro-OMeTAD, 22 μL Li-TFSI solution (520 mg dissolved in 1 ml acetonitrile), 20 μL Co-TFSI solution (375 mg Co-TFSI dissolved in 1 ml acetonitrile) and 30 μL 4-tert-butylpyridine to 1 mL chlorobenzene and shake in air at 25 °C for 12 h.

[0066] Step 8, preheat the prepared perovskite on a 40°C hot plate for 3 min, take 6.0 μL of Spiro-OMeTAD solution and drop it on the perovskite film, and scrape it forward at a speed of 1.5 m / min with a scraper, and the distance between the scraper and the substrate is 60 μm.

[0067] Step 9: Deposit a gold top electrode with a thickness of about 70 nm on the hole transport layer by thermal evaporation, with a vacuum degree of 9×10 –4 Pa, the evaporation rate is about 0.05nm / s. After the evaporation is completed, the battery is cooled in the vacuum chamber for 30 minutes and then taken out. The effective area of ​​each individual battery is 0.09cm 2 .

[0068] Example 1

[0069] Preparation of FA by blade coating in atmospheric environment 1-x-y C Sx MA y PbI 3-x Br x The specific steps of perovskite solar cells are as follows:

[0070] Step 1, cleaning and drying a fluorine-doped tin oxide (FTO) glass substrate for use as a conductive substrate;

[0071] Step 2, immerse the FTO / glass substrate in a TiCl aqueous solution at 70°C for 1 hour. Then rinse the grown TiO2 with deionized water to prevent the TiO2 on its surface from continuing to grow. An overly thick electron transport layer will hinder charge transfer. The thickness of the electron transport layer is 20nm. Blow dry the rinsed TiO2 substrate with an air gun, and then place it on a hot plate at 200°C for annealing for 0.5h to remove moisture from the TiO2 surface and obtain a dense TiO2 electron transport layer.

[0072] Step 3, the preparation of the perovskite precursor solution is as follows: 0.7M perovskite compounds FAI, CsBr, PbI2 and MACl are dissolved in 1mL of a mixed solvent at a molar ratio of 0.95:0.05:1:0.3, wherein the solvent composition is N,N-dimethylformamide: dimethyl sulfoxide: 2-methyltetrahydrofuran = 8:1:1, and 0.15% molar fraction of (3,5-difluorophenyl) potassium trifluoroborate is added to the perovskite solution to form an intermediate engineering perovskite solution, and 5% molar ratio of DMAPbI3 is added to the perovskite solution to replace PbI2 to regulate the perovskite crystal growth process.

[0073] Step 4, place the FTO / TiO2 substrate on a 60°C hot plate for preheating for 3 minutes, then drop 8.5μL of FAPbI3 precursor solution on the TiO2 / FTO substrate, and scrape it forward at a speed of 1.5m / min under the action of a scraper, and the distance between the scraper and the substrate is 80μm. The perovskite film after scraping is immediately blown to accelerate the evaporation of the solvent, thereby reducing water erosion and promoting perovskite crystallization. The blowing process uses an airflow at a temperature of 30°C, a flow rate of 20m / s, and a duration of 8s. After scraping, the perovskite film is immediately transferred to a 150°C hot plate for heating for 15 minutes to promote the subsequent growth of perovskite to obtain a perovskite film.

[0074] Step 5, prepare a passivating agent solution of perovskite: dissolve 0.0030 mg of phenylethylammonium iodide (PEAI) in 1 mL of isopropanol, shake for 12 h in an atmospheric environment at 25° C., and set aside.

[0075] Step 6: Preheat the prepared perovskite on a hot plate at 40°C for 3 minutes. At room temperature, drop 6.0 μL of PEAI solution on the perovskite film and scrape it forward at a speed of 1.5 m / min with a scraper. The distance between the scraper and the substrate is 60 μm.

[0076] Step 7, preparation of hole transport layer solution: add 90 mg Spiro-OMeTAD, 22 μL Li-TFSI solution (520 mg dissolved in 1 ml acetonitrile), 20 μL Co-TFSI solution (375 mg Co-TFSI dissolved in 1 ml acetonitrile) and 30 μL 4-tert-butylpyridine to 1 mL chlorobenzene and shake in air at 25 °C for 12 h.

[0077] Step 8, preheat the prepared perovskite on a 40°C hot plate for 3 min, take 6.0 μL of Spiro-OMeTAD solution and drop it on the perovskite film, and scrape it forward at a speed of 1.5 m / min with a scraper, and the distance between the scraper and the substrate is 60 μm.

[0078] Step 9: Deposit a gold top electrode with a thickness of about 70 nm on the hole transport layer by thermal evaporation, with a vacuum degree of 9×10 –4 Pa, the evaporation rate is about 0.05nm / s. After the evaporation is completed, the battery is cooled in the vacuum chamber for 30 minutes and then taken out. The effective area of ​​each individual battery is 0.09cm 2 .

[0079] Figure 1Schematic diagram of the crystallization of the perovskite film prepared by the method described in Example 1 of the present invention and Comparative Example 1 before and after annealing. DMAPbI3 is introduced into the perovskite precursor solution. In the film after scraping, DMAPbI3 will form an intermediate phase. After high-temperature annealing (150°C), these intermediate phases decompose, fill the vacancy defects and occupy the perovskite lattice position, and transform into a cubic phase of FA 1-x-y C Sx MA y PbI 3-x Br x perovskite phase, thereby filling the lattice defects in situ during the perovskite growth process.

[0080] Figure 2 The scanning electron microscope images of the perovskite film prepared by the method described in Example 1 and Comparative Example 1 of the present invention before and after annealing. Before annealing, the perovskite film of Comparative Example 1 shows a relatively small FAPbI3 grain size. In contrast, due to the addition of DMAPbI3, the grain size of the film of Example 1 is significantly increased. This result fully demonstrates the important role of DMAPbI3 in delaying crystal growth and expanding crystal size. In addition, it is observed that there is a needle-shaped 1D DMAPbI3 intermediate phase in the film of the optimized group. The formation of this intermediate phase is common in the CsPbI3 processing process, mainly due to its lower formation energy, which can effectively optimize crystal growth and passivate defects.

[0081] Figure 3 The NMR images of the perovskite films prepared by the methods described in Example 1 and Comparative Example 1 before and after annealing are shown in FIG. 1 H spectrum, the optimized film has a chemical shift of δ = 8.17ppm corresponding to –NH2 in DMA + – Related NMR peaks. After annealing, the DMA signal still exists, which indicates that there are DMA residues in the final perovskite film. The residue of DMA is due to the fact that part of DMA occupies the atomic lattice position in the perovskite film.

[0082] Figure 4 The in-situ ultraviolet-visible (UV-vis) absorption spectra of the perovskite films prepared by the methods described in Example 1 of the present invention and Comparative Example 1 during the doctor blade coating process show that the nucleation window of the perovskite in Example 1 is significantly extended compared to that in the control group (stage II). This is because the decomposition of the DMAPbI3 intermediate phase requires additional energy, which increases the energy barrier for perovskite nucleation.

[0083] Figure 5 The in-situ photoluminescence (PL) spectra of the perovskite films prepared by the methods described in Example 1 and Comparative Example 1 during annealing indicate that DMAPbI3 can repair defects in situ. This mechanism is mainly attributed to DMA+ and I - The ions effectively fill vacancy defects during crystal growth, thereby improving the quality of the perovskite film.

[0084] Figure 6 The PL lifetime mapping results of the perovskite films prepared by the methods described in Example 1 of the present invention and Comparative Example 1 further prove that the non-radiative recombination is effectively and uniformly suppressed in the film of Example 1.

[0085] Figure 7 The current density-voltage (JV) curves and the statistical distribution of photovoltaic device performance parameters (photovoltaic conversion efficiency (PCE), fill factor (FF) and series resistance (R)) of the perovskite solar cells prepared by the method described in Example 1 of the present invention and Comparative Example 1 are shown in FIG. S ), the specific device performance parameters are shown in Table 1. The PCE of the device in Comparative Example 1 is 21.57%, and the fill factor (FF) is 73.88%. In contrast, the device in Optimized Example 1 exhibits a more superior PCE of 23.13%, and its FF is 81.42%, which is significantly improved. Since the intermediate optimization strategy effectively improves the crystallization quality of the perovskite film and can in-situ passivate the vacancy defects in the film, the charge extraction capability is significantly enhanced. By fitting the JV parameters, the R S It was reduced from 78.23Ω to 52.87Ω, a decrease of 30%.

[0086] Table 1. Photovoltaic parameters of FAPbI3 best performance PSCs of Example 1 and Optimization Example 1

[0087]

[0088] Example 2

[0089] In this embodiment, the molar amount of DMAPbI3 added is 1% of the molar amount of PbI2, and the rest is the same as in Example 1.

[0090] Example 3

[0091] In this embodiment, the molar amount of DMAPbI3 added is 10% of the molar amount of PbI2, and the remaining parts not involved are the same as those in Example 1.

[0092] Example 4

[0093] In this embodiment, the molar amount of DMAPbI3 added is 20% of the molar amount of PbI2, and the remaining parts not involved are the same as those in Example 1.

[0094] Example 5

[0095] In this embodiment, the molar amount of DMAPbI3 added is 30% of the molar amount of PbI2, and the remaining parts not involved are the same as those in Example 1.

[0096] Example 6

[0097] In this embodiment, before the perovskite precursor solution is scraped, the FTO / TiO2 substrate is placed on a hot plate at 40°C for preheating for 3 minutes, and the remaining parts are the same as those in Example 1.

[0098] Example 7

[0099] In this embodiment, before the perovskite precursor solution is scraped, the FTO / TiO2 substrate is placed on a hot plate at 80°C for preheating for 3 minutes, and the remaining parts are the same as those in Example 1.

[0100] Example 8

[0101] In this embodiment, before the perovskite precursor solution is scraped, the FTO / TiO2 substrate is placed on a hot plate at 120°C for preheating for 3 minutes, and the remaining parts are the same as those in Example 1.

[0102] Example 9

[0103] In this embodiment, during the scraping process of the perovskite precursor solution, the distance between the scraper and the surface of the TiO2 electron transport layer is 10 μm, and the remaining parts not involved are the same as in Example 1.

[0104] Example 10

[0105] In this embodiment, during the scraping process of the perovskite precursor solution, the distance between the scraper and the surface of the TiO2 electron transport layer is 50 μm, and the remaining parts not involved are the same as in Example 1.

[0106] Embodiment 11

[0107] In this embodiment, during the scraping process of the perovskite precursor solution, the distance between the scraper and the surface of the TiO2 electron transport layer is 500 μm, and the remaining parts not involved are the same as those in Embodiment 1.

[0108] Example 12

[0109] In this embodiment, after the perovskite precursor solution is coated, the air flow temperature is 20° C., the air flow rate is 10 m / s, and the duration is 30 s.

[0110] Embodiment 13

[0111] In this embodiment, after the perovskite precursor solution is coated, the air flow temperature is 30° C., the air flow rate is 50 m / s, and the duration is 15 s.

[0112] Embodiment 14

[0113] In this embodiment, after the perovskite precursor solution is coated, the air flow temperature is 40° C., the air flow rate is 100 m / s, and the duration is 3 s.

[0114] Embodiment 15

[0115] In this embodiment, x is 0.05, y is 0.02, and the perovskite absorption layer is FA 0.93 Cs 0.05 MA 0.02 PbI 2.95 Br 0.05 .

[0116] Example 16

[0117] In this embodiment, x is 0.05, y is 0.06, and the perovskite absorption layer is FA 0.89 Cs 0.05 MA 0.06 PbI 2.95 Br 0.05 .

[0118] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A printing method for preparing high-efficiency perovskite solar cells, characterized in that: The following steps are involved: Step 1, pre-treating the FTO glass substrate; Step 2, immersing the FTO glass substrate in a TiCl4 aqueous solution to grow TiO2, and preparing a TiO2 electron transport layer after annealing; Step 3, dissolving FAI, CsBr, PbI2 and MACl in a solvent according to a set molar ratio, wherein the solvent is a mixed solution of N,N-dimethylformamide, dimethyl sulfoxide and 2-methyltetrahydrofuran, and then adding (3,5-difluorophenyl) potassium trifluoroborate to obtain an intermediate engineering perovskite solution, adding DMAPbI3 to the intermediate engineering perovskite solution, and stirring to obtain FAI added with DMAPbI3 1-x-y C Sx MA y PbI 3-x Br x Perovskite precursor solution, FA 1-x-y C Sx MA y PbI 3-x Br x In the example, x is 0.05 and y ranges from 0.02 to 0.06; Step 4, adding a perovskite precursor solution dropwise onto the TiO2 electron transport layer, applying the perovskite precursor solution by scraping with a scraper, blowing the solution after scraping, and annealing the solution after blowing to obtain a perovskite absorption layer; Step 5, preparing a Spiro-OMeTAD hole transport layer on the perovskite absorption layer; Step 6: Prepare a metal electrode on the hole transport layer.

2. The printing preparation method of a high-efficiency perovskite solar cell according to claim 1, characterized in that: In step 3, the added molar amount of DMAPbI3 is 1-30% of the molar amount of PbI2.

3. The printing preparation method of a high-efficiency perovskite solar cell according to claim 1, characterized in that: In step 3, the volume ratio of N,N-dimethylformamide, dimethyl sulfoxide and 2-methyltetrahydrofuran is (5-8):1:(1-4).

4. The printing preparation method of a high-efficiency perovskite solar cell according to claim 1, characterized in that: In step 3, the molar fraction of potassium (3,5-difluorophenyl) trifluoroborate in the perovskite precursor solution is 0.15-3%.

5. The printing preparation method of a high-efficiency perovskite solar cell according to claim 1, characterized in that: In step 4, the FTO glass substrate and the TiO2 electron transport layer were preheated on a hot plate at 40-120°C before scraping.

6. The printing preparation method of a high-efficiency perovskite solar cell according to claim 1, characterized in that: In step 4, during the coating process, the distance between the scraper and the surface of the TiO2 electron transport layer is 10-500 μm.

7. The printing preparation method of a high-efficiency perovskite solar cell according to claim 1, characterized in that: In step 4, during the blowing process, the air flow temperature is 20-40°C, the flow rate is 10-100m / s, and the duration is 3-30s.

8. The printing preparation method of a high-efficiency perovskite solar cell according to claim 1, characterized in that: In step 4, the annealing temperature is 150° C. and the annealing time is 15 min.

9. The printing preparation method of a high-efficiency perovskite solar cell according to claim 1, characterized in that: In step 5, before preparing the Spiro-OMeTAD hole transport layer, a PEAI passivation layer is prepared.

10. A high-efficiency perovskite solar cell prepared by the preparation method according to any one of claims 1 to 9, characterized in that: It includes FTO glass substrate, TiO2 electron transport layer, FA 1-x-y C Sx MA y PbI 3-x Br x Perovskite absorber layer, Spiro-OMeTAD hole transport layer and metal electrode.

Citation Information

Patent Citations

  • Preparation method of Cs&lt;n&gt;FA&lt;1-n&gt;PbX&lt;3&gt; perovskite thin film

    CN111129319A

  • Perovskite solar cell and preparation method thereof

    CN113224241A

  • Efficient perovskite solar cell and preparation method thereof

    CN113363390A

  • Perovskite precursor solution, preparation method thereof and perovskite solar cell

    CN114141953A

  • Large-area perovskite thin film and preparation method and application thereof

    CN117956877A